Pharmacists’ workplace safety during the COVID-19 pandemic (One Health & Risk Management, 2023)
Introduction. Pharmacists are likely to be exposed to lower risks in healthcare emergencies compared to health workers from other health sectors (primary care, emergency care or hospitals). This present research has assessed the risks of pharmaceutical workers during the COVID-19 pandemic, as well as analysed the safety measures applied within the workplace in order to present recommendations for the protection of pharmacists and reducing the risk factors.Material and methods. A quantitative and a qualitative study was carried out during the present research. The quantitative study was carried out on a sample of 336 pharmacists and pharmacist assistants from different pharmacies. The qualitative study was based on in-depth interviews with 8 representatives from different areas of the pharmaceutical sector.  Results.  The study results reflected several aspects regarding the roles of pharmacists, the risks they were subjected to, and the morbidity of pharmacists during the COVID-19 pandemic, as well as in terms of provision and maintaining safety workplace conditions.Conclusions. Several recommendations were developed based on the analysis and conclusions of the research, which aimed at increasing the safety of pharmaceutical workers in public health emergencies such as epidemics or pandemics.